Integrin β3 Leu33Pro polymorphism increases BRCA1‐associated ovarian cancer risk - Jakubowska, Anna (BMJ Group, 2007)
Integrins are heterodimeric transmembrane glycoproteins that function as key adhesion and cell signalling receptors. A functional polymorphism in the integrin β3 subunit encoded by the ITGB3 gene, Leu33Pro, has been shown to modify a variety of traits of β3‐expressing cells. To analyse the role of this functional polymorphism in modifying BRCA1‐associated ovarian and breast cancer risks, a case–control study was performed among Polish BRCA1 mutation carriers including 319 breast cancer cases, 146 ovarian cancer cases and 290 controls unaffected by breast and ovarian cancer, in situ breast cancer or any other kind of cancer. Genotyping analysis was performed using PCR‐based restriction fragment length polymorphism analysis. Odds ratios were calculated using univariate and multivariate logistic regression, taking into account a series of confounding variables, including the presence of related study subjects, that potentially could have biased any association. The results revealed that the ITGB3_Leu33Pro polymorphism was associated with a 2.5‐fold increased risk of ovarian cancer, whereas no association with breast cancer risk was found. Thus, it appears that the ITGB3_Leu33Pro polymorphism may potentially increase the risk of ovarian cancer in Polish women with an inherited BRCA1 mutation.